Generative Artificial Intelligence Summaries to Facilitate Emergency Department Handoff - Genes, Nicholas; Simon, Gregory; Koziatek, Christian; Kim, Jung G.; Woo, Kar-mun; Dahn, Cassidy; Chan, Leland; Wiesenfeld, Batia (Applied Clinical Informatics, 2025)
Emergency department (ED) handoff to inpatient teams is a potential source of error. Generative artificial intelligence (AI) has shown promise in succinctly summarizing large quantities of clinical data and may help improve ED handoff.Our objectives were to: (1) evaluate the accuracy, clinical utility, and safety of AI-generated ED-to-inpatient handoff summaries; (2) identify patient and visit characteristics influencing summary effectiveness; and (3) characterize potential error patterns to inform implementation strategies.This exploratory study evaluated AI-generated handoff summaries at an urban academic ED (February–April 2024). A Health Insurance Portability and Accountability Act-compliant GPT-4 model generated summaries aligned with the IPASS framework; ED providers assessed summary accuracy, usefulness, and safety through on-shift surveys.Among 50 cases, median quality and usefulness scores were 4/5 (standard error = 0.13). Safety concerns arose in 6% of cases, with issues including data omissions and mischaracterizations. Consultation status significantly affected usefulness scores (p < 0.05). Omissions of relevant medications, laboratory results, and other essential details were noted (n = 6), and emergency medicine clinicians disagreed with some AI characterizations of patient stability, vitals, and workup (n = 8). The most common response was positive impressions of the technology incorporated into the handoff process (n = 11).This exploratory provider-in-the-loop model demonstrated clinical acceptability and highlighted areas for refinement. Future studies should incorporate recipient perspectives and examine clinical outcomes to scale and optimize AI implementation.
Keywords: emergency medicine; communication; artificial intelligence; safety; handoffs; electronic health records